The Melancholic Stimmung between Imaginary and Epistemology. Pop Icons and Wonderful Monstrosities - De Feo, Linda (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2021)
The melancholy is an aesthetic category oscillating between feeling and emotion. Before to be mediated by conceptual speculation, the melancholic tone took rooted in the archè of Western imaginary. The object of the reflection will be the indissolubility of its relationship both with expressive modes of cultural representations and with fundamental traits of the history of ideas. At least since the age of nihilism, melancholy is conceived as a theoretical model based on the absence of meaning in human existence. It is understood as a cognitive paradigm that insists on disenchantment alongside regret for an allegedly lost ontological foundation. The creativity is a significant cultural reflection of social change. It produces communicative objects, elitist or popular, tries to delineate paths of meaning and identifies traces of destinations. The paper will be focused in particular on the relationship between melancholic affection and science fiction, segment of contemporary pop imaginative heritage, interpretative mode of a metaphysics of virtuality inspired by a chimerical techno-cultural vocation. Fragment of an alchemic genre of narrative, the dystopian science fiction actually represents the unstoppable flow of the life redefined as information, code and symbol. It unravels the knot between the need of the human beings to imagine and the Cartesian reduction of the subjective action to mere calculation. Thus, it resolvs the conflict between the opacity of res extensa and the brilliance of res cogitans. The science fiction demonstrates that allegories and metaphores allow the imagination to adhere to harsh depths of reality and gives the inner space the possibility to show itself, to become monstrous, to live the kaleidoscopic wonder of all irrational tensions, translated into deformations, not always horrific, of experience. The imaginary is a free to give shape to a duty, of which the subject perceives the gravity. It imposes to interpret constantly the technological otherness, it recognizes the problematic existence of immutable essences in the human being and it emphasizes the unfolding in homo technologicus of the aspiration to overcome the biological finiteness.